Exogenous γ-aminobutyric acid (GABA) mitigated salinity-induced impairments in mungbean plants by regulating their nitrogen metabolism and antioxidant potential - Ullah, Abd; Ali, Iftikhar; Noor, Javaria; Zeng, Fanjiang; Bawazeer, Sami; Eldin, Sayed M; Asghar, Muhammad Ahsan; Javed, Hafiz Hassan; Saleem, Khansa; Ullah, Sami; Ali, Haider (Frontiers in Plant Science, 2023)
Increasing soil salinization has a detrimental effect on agricultural productivity. Therefore, strategies are needed to induce salinity-tolerance in crop species for sustainable food production. γ-aminobutyric acid (GABA) plays a key role in regulating plant salinity stress tolerance. However, it remains largely unknown how mungbean plants (Vigna radiata L.) respond to exogenous GABA under salinity stress. Thus, we evaluated the effect of exogenous GABA (1.5 mM) on growth and physio-biochemical response mechanism of mungbean plants to saline stress (0-, 50-, and 100 mM [NaCl and Na2SO4, at a 1:1 molar ratio]). Increased saline stress adversely affected mungbean plants' growth and metabolism. For instance, leaf-stem-root biomass (34- and 56%, 31- and 53%, and 27- and 56% under 50- and 100 mM, respectively]) and chlorophyll concentrations declined. Carotenoid level, increased (10%) at 50 mM and remained unaffected at 100 mM level. Hydrogen peroxide (H2O2), malondialdehyde (MDA), osmolytes (soluble sugars, soluble proteins, proline), total phenolic content, and enzymatic activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase (POD), glutathione reductase (GTR), and polyphenol oxidation (PPO) were significantly increased. In leaves, salinity caused a significant increase in Na+ concentration but a decrease in K+ concentration, resulting in a low K+/Na+ concentration (51- and 71% under 50- and 100- mM stress). Additionally, nitrogen concentration and the activities of nitrate reductase (NR) and glutamine synthetase (GS) decreased significantly. The reduction in glutamate synthase (GOGAT) activity was only significant (65%) at 100 mM stress. Exogenous GABA decreased Na+, H2O2, and MDA concentrations but enhanced photosynthetic pigments, K+ and K+/Na+ ratio, N metabolism, osmolytes, and enzymatic antioxidant activities, thus reducing salinity-associated stress damages, resulting in improved growth and biomass. Exogenous GABA may have improved the salinity tolerance of mungbean plants by maintaining their cellular morpho-physiological and reducing the accumulation of harmful substances under salinity. Future molecular studies can contribute to a better understanding of the molecular mechanisms by which GABA regulates mungbean salinity tolerance.